Proteomic insights into mycobacterial responses to elevated riboflavin reveal a role for flavin-sequestering proteins in flavin homeostasis - Oketade, Nurudeen; Dobos, Karen M. (Frontiers in Tuberculosis, 2025)
Riboflavin biosynthesis is essential for most microorganisms, yet its production is tightly regulated due to the potential toxic effect of riboflavin and its derivatives. While regulatory mechanisms for this process have been described in other organisms, none has been identified in mycobacteria. Uncovering such a mechanism will be critical to fully exploit the riboflavin biosynthetic pathway as a pharmacological target. We previously observed that Mycobacterium tuberculosis (Mtb) and Mycolicibacterium smegmatis (Msm) can grow successfully under elevated riboflavin levels, prompting an investigation into how mycobacteria tolerates high intracellular riboflavin. Using a bioinformatic approach of proteomic data, we explored the global proteomic response of Mtb and Msm to elevated riboflavin. Our results revealed increased abundance of know flavin sequesters in response to high riboflavin levels, suggesting a role in flavin homeostasis. Using a transcription regulatory network analysis, we observed the employment of similar regulatory networks, most notably DosR, in both Mtb and Msm in response to elevated riboflavin. We also identified a potential link between the riboflavin induced response and isoniazid resistance mechanisms, warranting further investigation. Overall, this study provides evidence for the involvement of flavin sequesters in maintaining flavin homeostasis and highlights the potential regulatory role of DosR in this process.